Sustainable development principles in U.S. sport management graduate programs. Issue 1 (2nd January 2022) - Ličen, Simon; Jedlicka, Scott R.
ABSTRACT: This study assesses the engagement of academic programs in sport management with global problems by using the United Nations' Sustainable Development Goals as a proxy measure of these problems, and gauges the degree to which sport management programs are positioning themselves as providers of knowledge and expertise in the area of sustainable development. To this end, the authors examined the program descriptions, learning outcomes and curricula of 84 graduate programs in sport management or closely related fields at 65 R1 universities in the United States. Using inductive thematic analysis, they identified seven themes that are shared across multiple program curricula. The seven themes were labeled: sport sociology and sport ethics; globalization and economic growth; sport for development and peace; health; climate, environment and sustainability; gender; and inequality, discrimination and social justice. The overall results indicate that the discipline has coalesced around a key set of skills and content areas. This standardization may come at the expense of adaptability and responsiveness to changes in sport and in society. Academic programs are generally unwilling to depart from a twentieth-century model of education built around a supposition that the sport manager's primary responsibilities are revenue generation and liability mitigation. As the unsustainability of late capitalism becomes increasingly difficult to ignore, students and educators will find it correspondingly complicated to reconcile the contradiction between sport-as-business-enterprise and the notion that sport itself can contribute to social or moral development. This long-standing compromising attitude and failure to acknowledge the need for wholesale change will only require much more disruptive and perhaps radical reform in the future. Faced with pressure from various stakeholders, many sport organizations employ sustainability units or departments. Although imperfect, these efforts often exceed those made by academic programs.